The impact of the mother-daughter relationship on the risky sexual behaviors of female adolescents - Hartenstein, Jaimee L. (Kansas State University, 2012)
Female adolescent sexual behavior has several potential negative life consequences including: pregnancy, sexually transmitted infection, and HIV/AIDS. Educating parents on how they play a role in the decision-making process regarding the sexual behavior of their adolescent daughters has important implications for Family Life Educators. This thesis explores maternal influence on the risky sexual behavior of female adolescents related to age at first sexual intercourse, contraceptive use, and number of partners. ANOVA was used to explore the relationships between a variety of aspects in the mother-daughter relationship. Findings show there are associations between time spent together, perceptions of closeness, and communication in mother-daughter relationships, and contraceptive use at first and most recent intercourse and total number of partners.
Keywords: Female adolescents; Risky sexual behaviors; Mother-daughter relationship; Social Research (0344); Social Sciences Education (0534)